Effectiveness of the handgrip test for assessing readiness in national level basketball players: a cohort study - Ruscello, B.; Santolamazza, F.; Castagna, C.; Pistello, A.; Gabrielli, P. R.; Ceccacci, M.; Mecangeli, G.; Del Bene, P.; D'Ottavio, S. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: Assessing player readiness is crucial in elite basketball. This study aims to provide a practical method for monitoring player readiness through the handgrip test and identify associations with wellness scales. METHODS: Fifteen players (age: 25.3±3.3 years; weight: 92.2±11.8 kg; height: 1.94±0.09 m; BMI: 24.3±1.8 kg/m2; experience: 6.5±3.4 years) from an elite basketball team participated in this cohort study, which was conducted over 9 weeks of training and official competitions. All players were medically cleared and injury-free for three months prior. Daily psychometric questionnaires assessed different aspects of wellness using analog scales, combined with a handgrip test. Training cycles were developed according to the Game-Day method. RESULTS: All parameters investigated, except the handgrip test, (means ranging from 53.43±8.06 kg to 54.03±7.79 kg) showed significant variations in the weekly training cycle (P<0.05). The linear regression results indicate that while the overall model is statistically significant (P=0.039), the predictive power of the individual independent variables is not strong, with the model able to explain approximately 4.13% of the variability in the dependent variable "Handgrip." The calculation of the minimal detectable change (MDC) confirmed that for this variable, on average, significant changes (approximately 6.77 kg) are generally required to be noteworthy. CONCLUSIONS: This study demonstrates that the handgrip test is not an effective tool for objectively assessing player readiness in elite basketball. Regular monitoring using this method cannot help in making informed decisions about training and competition readiness. Conversely, psychometric have shown stronger sensitivity in determining player status during the weekly training cycle.